192k views
1 vote
Write the expression with a single base and single positive exponent then simplify. y^{-4}(y^2)^2 The base is AnswerThe exponent is AnswerThis simplifies to Answer

Write the expression with a single base and single positive exponent then simplify-example-1
User Purefn
by
5.2k points

1 Answer

0 votes

The expression is given as,


y^(-4)\cdot(y^2)^2

Consider the following laws of exponents,


\begin{gathered} (x^m)^n=x^(mn) \\ x^m\cdot x^n=x^(m+n) \end{gathered}

Use the above laws to simplify the expression as follows,


\begin{gathered} =y^(-4)\cdot(y^(2\cdot2)) \\ =y^(-4)\cdot(y^4) \\ =y^(-4+4) \\ =y^0 \\ =1 \end{gathered}

The value 1 can be expressed as,


=1^1

Therefore, the base is 1, and the exponent is also 1.

User Drew Dahlman
by
5.4k points